The RSU Access Problem Based on Evolutionary Game Theory for VANET - Di Wu; Yan Ling; Hongsong Zhu; Jie Liang (International Journal of Distributed Sensor Networks)
We identify some challenges in RSU access problem. There are two main problems in V2R communication. (1) It is difficult to maintain the end-to-end connection between vehicles and RSU due to the high mobility of vehicles. (2) The limited RSU bandwidth resources lead to the vehicles' disorderly competition behavior, which will give rise to multiple RSUs having overlap area environment where RSU access becomes crucial for increasing vehicles' throughput. Focusing on the problems mentioned above, the RSU access question in the paper is formulated as a dynamic evolutionary game for studying the competition of vehicles in the single community and among multiple communities to share the limited bandwidth in the available RSUs, and the evolutionary equilibrium evolutionary stable strategy (ESS) is considered to be the solution to this game. Simulation results based on a realistic vehicular traffic model demonstrate the evolution process of the game and how the ESS can affect the network performance.